Technology used in the Agricultural Sector: A Review - Sharma, Suraj; Singh, Karanjot; Kukreja, Deepak; Singh, Harkirat; Raj, Aditya (Journal of Advanced Research in Information Technology, Systems and Management; Vol 6 No 1 (2022): Journal of Advanced Research in Information Technology, Systems and Management, 2022)
Agriculture needs effective utilization of technology to accelerate production and of individuals. The main purpose of this research paper is to understand, how to make effective use of technologies in the agricultural sector. There are numerous types of technologies that are made use of to enhance productivity. The main areas that have been taken into account are, factors relating to adoption of technologies, types of technologies, technologies used in the agricultural sector, advanced agricultural technologies used in the present existence, areas of information technology and role of information technology in agricultural education management. For efficient growth and development of the agricultural sector, there is a need to familiarize with new technologies, like biotechnology, nanotechnology, high-tech protected cultivation and modern irrigation methods to accelerate production. These technologies, when utilized in an appropriate manner, would prove to be beneficial in improving productivity and profitability. Usage of technology would enhance in sustaining livelihood opportunities for the farmers. How to cite this article: Sharma S, Singh K, Kukreja D et al. Technology used in the Agricultural Sector: A Review. J Adv Res Info Tech Sys Mgmt 2022; 6(1): 13-24.